PENGEMBANGAN MEDIA PEMBELAJARAN E-LEARNING MENGGUNAKAN MOODLE BERBASIS E-MODUL PADA PEMBELAJARAN INTALASI PENERANGAN LISTRIK UNTUK KELAS XI TITL SMK SWASTA IMELDA MEDAN - Feber Dhika Purba; Hamonangan Tambunan (JEVTE: Journal of Electrical Vocational Teacher Education, 2021)
Abstract This study aims to know the feasibility of media, as well as to know the response to the development of e-learning media using moodle-based e-modules on the learning of electrical lighting installations at SMKS Imelda Medan. This e-learning development uses addie development model adapted from Mollenda and Reiser (2003). namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. E-learning feasibility assessment is conducted by material experts, media experts, and teachers as respondents. Data collection techniques used are questionnaire techniques to obtain quantitative data as primary data and qualitative data in the form of suggestions or comments as data for e-learning improvements. Quantitative data obtained is then converted into qualitative data using ideal assessment criteria. The results showed that: e-learning has "feasible" criteria from material experts with an average assessment of 4.00, from e-learning media experts have "feasible" criteria with an average rating of 4.13; e-learning trial results to respondents showed that e-learning has a "high acceptance" criteria with an average rating of 4.05. Based on the results of the development research obtained, it can be concluded that the development of e-learning using moodle-based e-modules in SMKS Imelda Medan is feasible to be developed. Key Words: E-Learning Moodle, learning media, E-module AbstrakPenelitian ini bertujuan untuk mengetahui kelayakan media, serta mengetahui respon terhadap pengembangan media e-learning menggunakan moodle berbasis e-modul pada pembelajaran instalasi penerangan listrik di SMKS Imelda Medan. Pengembangan e-learning ini menggunakan model pengembangan ADDIE diadaptasi dari Mollenda dan Reiser (2003). yakni: (1) analisis, (2) desain, (3) pengembangan, (4) implementasi, dan (5) evaluasi. Penilaian kelayakan e-learning dilakukan oleh ahli materi, ahli media, dan guru sebagai responden. Teknik pengumpulan data yang digunakan adalah teknik angket untuk memperoleh data kuantitatif sebagai data primer dan data kualitatif berupa saran atau komentar sebagai data untuk perbaikan e-learning. Data kuantitatif yang diperoleh kemudian dikonversi menjadi data kualitatif menggunakan kriteria penilaian ideal. Hasil penelitian menunjukkan bahwa: e-learning memiliki kriteria “layak” dari ahli materi dengan rerata penilaian 4.00, dari ahli media e-learning memiliki kriteria “layak” dengan rerata penilaian 4.13; hasil uji coba e-learning kepada responden menunjukkan bahwa e-learning memiliki kriteria “akseptansi tinggi” dengan rerata penilaian 4.05. Berdasarkan hasil dari penelitian pengembangan yang diperoleh maka dapat disimpulkan bahwa pengembangan e-learning menggunakan moodle berbasis e-modul di SMKS Imelda Medan layak untuk dikembangkan. Kata Kunci: E-Learning Moodle, Media Pembelajaran, E-Modul